Jump start Sinatra get up to speed with Sinatra in a weekend - Jones, Darren (SitePoint Pty. Ltd., 2013)
Annotation
Includes bibliographical references and index
Keywords: Ruby (Computer program language); Web site development; Internet programming; Ruby (Langage de programmation); Sites Web; Développement; Programmation Internet; COMPUTERS; Digital Media; General; COMPUTERS; Interactive & Multimedia; COMPUTERS; Web; Site Design; COMPUTERS; Web; User Generated Content